2021
DOI: 10.1039/d1an00767j
|View full text |Cite
|
Sign up to set email alerts
|

Potential and applications of capillary electrophoresis for analyzing traditional Chinese medicine: a critical review

Abstract: Capillary electrophoresis (CE) presents a promising prospect in analyzing traditional Chinese medicine (TCM) due to its low reagent consumption, high analysis speed, and enhanced efficiency. Herein, we review the employment...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 121 publications
0
11
0
Order By: Relevance
“…Notably, the results of this study also showed that high NRS score was also a high risk factor for postoperative complications of bladder cancer ( P < 0.05). This indicates that the nutritional status of the body is closely related to the incidence of postoperative complications in patients with malignant tumors [ 18 , 19 ]. Further comparison of the severity of complications among patients with different NRS-2002 scores showed that the incidence of intestinal obstruction and the total incidence of complications in the NRS ≥3 group were significantly higher than those in the NRS <3 group ( P < 0.05), with no significant differences in other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the results of this study also showed that high NRS score was also a high risk factor for postoperative complications of bladder cancer ( P < 0.05). This indicates that the nutritional status of the body is closely related to the incidence of postoperative complications in patients with malignant tumors [ 18 , 19 ]. Further comparison of the severity of complications among patients with different NRS-2002 scores showed that the incidence of intestinal obstruction and the total incidence of complications in the NRS ≥3 group were significantly higher than those in the NRS <3 group ( P < 0.05), with no significant differences in other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Fast-track intravenous anesthesia combined with spinal-epidural anesthesia or nerve block anesthesia is commonly used in clinical anesthesia. Spinal-epidural anesthesia can theoretically be used for all surgical anesthetics except those below the head and for postoperative analgesia, but its safety is unsatisfactory [ 12 ]. The results of this study showed that there was no statistical difference between the two groups in the one-time success rate of the operation, and all patients were successful at one time.…”
Section: Discussionmentioning
confidence: 99%
“…Acyclovir and ganciclovir both showed good effects on abnormally high proportion of abnormal lymphocytes, proportion of lymphocytes, and white blood cell count, but ganciclovir showed better effects. Ganciclovir has a broader antiviral spectrum than acyclovir, and the DNA polymerase of the EBV is highly sensitive to both triphosphates of acyclovir and ganciclovir [ 13 , 14 ]. Ganciclovir is converted into activated triphosphate by thymidine kinase action in infected cells, which competitively inhibits viral DNA polymerase, terminates EBV-DNA prolongation, and inhibits replication of its viral products.…”
Section: Discussionmentioning
confidence: 99%